Cold-restraint- and TRH-induced ulcer models demonstrate different biochemical and morphological manifestations in gastric and hepatic tissues in rats role of calcitonin - (:unkn) unknown (SPRINGER, 1996)
In the present study, two ulcer models-central thyrotropin-releasing hormone (TRH) injection and cold-restraint stress (CRS) application-were compared. Animals were treated either with salmon calcitonin (sCT) or saline intracerebroventricularly (ICV) before CRS exposure or ICV TRH injection. In both models, besides ultrastructural properties, ulcer indexes and lipid peroxidation (LP) and glutathione (GSH) levels of liver and stomach were determined, While TRH treatment did not affect GSH and LP levels of the stomach and led to a slight decrease in hepatic GSH levels, CRS induced a marked reduction in gastric and hepatic GSH and an increase in LP levels of both tissues, sCT pretreatment prevented the reduction of gastric and hepatic GSH levels and morphological damage of both tissues in the CRS group, However, the same treatment did not prevent the TRH-induced reduction of hepatic GSH levels and, interestingly, it worsened the ultrastructural disturbances in the liver. Although sCT prevented macroscopic ulcer formation in both models, it did not totally reverse the microscopic effects of TRH.
Keywords: thyrotropin-releasing hormone; cold-restraint stress; liver; stomach; glutathione; lipid peroxidation; calcitonin; THYROTROPIN-RELEASING-HORMONE; NERVOUS-SYSTEM ACTION; ACID SECRETION; MEDULLARY SITES; SOLITARY TRACT; DORSAL VAGAL; STRESS; GLUTATHIONE; STIMULATION; ANALOG